EFFECTIVENESS OF WAYS TO PREVENT AND COMBAT DENGUE IN BRAZIL - e Silva, Anna Lya Godoi de Castro; Barra, Bruna Bandeira; Santos, Daniela Moraes; Matozinho, Darah Vità³ria Paiva; Damasceno, Felipe Freire Vieria; de Freitas, Gustavo Lustosa Elà³i; Pereira, Maria Sà´nia (CIPEEX, 2022)
DENGUE IS AN ENDEMIC ARBOVIRUS IN BRAZIL, TRANSMITTED THROUGH THE BITE OF AN INFECTED AEDES AEGYPTI MOSQUITO, WHICH AFFECTS THOUSANDS OF BRAZILIANS PER YEAR, REQUIRING A WIDE DEVELOPMENT OF FORMS OF PREVENTION AND COMBAT, MAINLY OF ITS VECTOR. IN THIS SENSE, THE PRESENT ANALYSIS IS A MINI INTEGRATIVE REVIEW, WHICH AIMS TO EVALUATE THE EFFECTIVENESS OF THE VARIOUS FORMS OF PREVENTION AGAINST DENGUE IN THE BRAZILIAN TERRITORY. FOR THE SELECTION OF SCIENTIFIC ARTICLES, WAS USED PUBMED AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AS A DATABASE, TAKING A FINAL SAMPLE CONSISTING OF 5 ARTICLES. IN THIS WAY, SEVERAL RESULTS WERE OBTAINED THAT PORTRAY THE METHODS OF FORMULATING POSTERS AND BOOKLETS, GARBAGE COLLECTION, GOVERNMENT MANAGEMENT, ACTION BY THE ACES AND CHAS, AND SOCIAL MOBILIZATION AS EFFECTIVE FORMS OF PREVENTION, BUT WHICH NEED TO BE REFORMULATED. FOR THE MOST PART, THAT WERE CONSONANTS IN THEIR EFFECTIVE AGAINST DENGUE. THEREFORE, IT IS EVIDENT THAT THE FORMS OF PREVENTION DEPEND ON SEVERAL FACTORS, CULMINATING IN A LOW PRACTICAL EFFECTIVENESS IN COMBATING CASES OF DENGUE.